Agrarian struggles in India after independence - Desai, A. R. (ed.) (Delhi OUP, 1986)
The struggles developing in the agrarian areas of the Indian Union, do exhibit certain features which are similar to those which prevailed during the British period. However, there are certain features which differentiate them and set them aside. They are fought for different objectives, for different demands and within different classes and against different types of State machinery.
Keywords: Struggle in India